Edukasi Pemberian Makanan Sehat Bergizi Pada Anak Sekolah Dasar Untuk Meningkatkan Kualitas Belajar Di MIN Gulai Bancah Kota Bukittinggi - Zilfi Yola Pitri (Jurnal Pengabdian Masyarakat, 2025)
According to the WHO (World Health Organization), regular breakfast intake in children has been proven to be associated with healthy body weight and intelligence in children. Breakfast activities, which consist of eating and drinking between waking up and 9:00 a.m., fulfill 15-30% of daily nutritional needs. This is related to blood glucose levels and brain function, especially concentration in learning in the morning. Glucose contained in breakfast plays a role in a person's memory (cognitive) mechanism, and nutrition is a food or drink substance needed for growth. Malnutrition that occurs at a young age has negative impacts on children, including: children are prone to mental fatigue, difficulty concentrating, low self-esteem, and decreased academic performance. Achievement or success in learning can be operationalized in the form of indicators, namely grades, study achievement index, graduation rates, graduation predicates, and the like. School-age children are an investment and the next generation of the nation. The quality of the nation in the future is determined by the quality of today's children. One effort to meet the nutritional needs of children is by providing healthy, nutritious food to them appropriately. The purpose of this community service activity is to educate elementary school children from grades 1 to 6 about the importance of a healthy and nutritious breakfast before going to school to increase their enthusiasm for learning. The target of this activity is 6th grade elementary school children. The methods applied in this outreach activity include: 1) initial observation and problem identification; 2) nutrition socialization and education; 3) healthy breakfast demonstration; 4) interactive games and educational quizzes; 5) evaluation and follow-up. This community service activity was carried out on October 15, 2025. Counseling on education about providing healthy and nutritious food to elementary school children to improve the quality of learning at MIN Gulai Bancah, Bukittinggi City. This needs to be held regularly, so that students' knowledge about the importance of breakfast before going to school is very important in improving the quality of learning and academic achievement at school.